THE COMBINATION OF HIGH FAT DIET AND MONOSODIUM GLUTAMATE ALTERING ADIPOGENESIS, BRAIN RESISTIN AND SERUM CORTISOL LEVEL IN FEMALE RAT - Aris Widayati; Dewi Mustika; Yhusi Karina Riskawati; Agustin Iskandar; Nia Kurnianingsih (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: The prevalence of obesity is increasing tremendously worldwide. Obesity is correlated with the consumption of a high-fat diet (HFD) and monosodium glutamate (MSG). Although the effect of MSG or HFD on inflammation has been established, lack of information about the effects of both combination on simultaneous systemic and brain inflammation that can be evaluated from cortisol serum and brain resistin level respectively. Objectives: This study aimed to investigate the effects of combining HFD and MSG on brain resistin, serum cortisol, lipid profiles, visceral weight, and body weight gain. Methods: Sixteen adult female rats were randomized into 4 groups consist of standard diet; HFD+MSG 0.05 mg/gBW, HFD+MSG 0.2 mg/gBW and HFD+MSG 0.35 mg/gBW. Lipid profiles were measured using automatic biochemical analyzer. Brain resistin and serum cortisol level were determined using enzyme-linked immunoassay. Results: The groups of HFD+MSG significantly have higher level of brain resistin (p<0.003), serum cortisol (p<0.01), total cholesterol (p<0.003) and visceral fat weight (p<0.05) than control group. Conclusion: The combination of HFD, and MSG generates obesity that led to systemic-brain alteration on inflammation. Further study is necessary to evaluate further the functional impact of both combinations on behavioral profiles.